Three-dimensional assessment of airway volumes in patients with unilateral cleft lip and palate - Bita Kiaee; Ludovica Nucci; Farzin Sarkarat; Ahmad Reza Talaeipour; Sara Eslami; Faezeh Amiri; Abdolreza Jamilian (SpringerOpen, 2021)
Abstract Background Considering the adverse consequences of respiratory insufficiency in cleft lip and palate (CLP) patients, this study aimed to assess the pharyngeal airway dimensions in 9-12-year-old patients with unilateral CLP. This historical cohort evaluated the cone-beam computed tomography (CBCT) scans of 30 patients with non-syndromic unilateral CLP between 9 and 12 years and 30 age- and sex-matched non-cleft controls. Three-dimensional (3D) images were reconstructed by the Mimics software, and the nasopharyngeal, oropharyngeal, and total airway volumes, as well as the minimal cross-sectional area of the airway (minAx), and posterior airway length (PAL) were all measured in the sagittal plane. Data were analyzed by the Student's t test. Results The oropharyngeal and the total airway volumes, as well as the minAx and PAL in CLP patients, were significantly smaller than the corresponding values in the control group (P < 0.05). Despite smaller nasopharyngeal airway volume in CLP patients than controls, this difference was not statistically significant (P > 0.05). Conclusions Nine- to twelve-year-old non-syndromic unilateral CLP patients have smaller pharyngeal airway dimensions than non-cleft controls, and are therefore at higher risk of respiratory insufficiency.